Finding Langston - Cline-Ransome, Lesa (New York : Holiday House, 2018)
Discovering a book of Langston Hughes' poetry in the library helps Langston cope with the loss of his mother, relocating from Alabama to Chicago as part of the Great Migration, and being bullied.
Keywords: Books and reading -- Fiction; Moving, Household -- Fiction; Bullying -- Fiction; African Americans -- Fiction; Single-parent families -- Fiction; Chicago (Ill.) -- History -- 20th century -- Fiction; Poetry